MODERN TRENDS IN THE DEVELOPMENT OF E-COMMERCE IN UZBEKISTAN - Khamraeva, Sayyora Nasimovna (THE INNOVATION ECONOMY, 2026)
This article examines the modern trends in the development of e-commerce in Uzbekistan within the context of the digital transformation of the economy. The study analyzes the key drivers of e-commerce growth, including the expansion of internet infrastructure, the development of digital payment systems, and increasing consumer demand for online services. Particular attention is paid to the role of innovative technologies such as artificial intelligence, Big Data, and blockchain in enhancing the efficiency and competitiveness of electronic commerce. The paper also identifies existing challenges, including logistics constraints, cybersecurity risks, and insufficient digital literacy among certain population groups. Based on the analysis of international experience and national conditions, the study proposes practical recommendations for improving the e-commerce ecosystem in Uzbekistan. The findings contribute to the development of effective strategies for strengthening the digital economy and expanding the participation of small and medium-sized enterprises in online markets.